2018
DOI: 10.24831/jai.v46i2.16538
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Genotipe Tomat Hasil Iradiasi Sinar Gamma di Dataran Rendah

Abstract: <p><em></em><em>ABSTRACT<br /><br />Bacterial wilt and fruit cracking are serious problems in tomatoes cultivation in the lowland area. This research aimed to evaluate the yield of M4 generation of tomatoes in the field and the incidence of bacterial wilt disease and fruit cracking in low altitude. The research was conducted at the IPB Experimental Field in Leuwikopo, Dramaga, Bogor, from December 2015 to April 2016. The experiment used a randomized complete block design wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…According to Mustafa et al (2017), the cracking resistance measured by the fruit cracking index in tomatoes is controlled by two double recessive epistatic genes. Romadhon et al (2018) reported that the percentage weight of cracking fruit and fruit cracking index was inherited with a high heritability value.…”
Section: Yield Components Of Tomato M7 Mutant Lines the Check Varietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Mustafa et al (2017), the cracking resistance measured by the fruit cracking index in tomatoes is controlled by two double recessive epistatic genes. Romadhon et al (2018) reported that the percentage weight of cracking fruit and fruit cracking index was inherited with a high heritability value.…”
Section: Yield Components Of Tomato M7 Mutant Lines the Check Varietiesmentioning
confidence: 99%
“…In previous studies, ten of the best M7 mutant lines were resulted from induced mutations and selected for yield improvement and adaptation to the lowlands. Romadhon et al (2018) reported that these mutant lines have better yield potential than the parents. Descriptors of quantitative characters, both morphological and agronomic, do not always provide genetic differences or similarities between genotypes because quantitative characters are influenced by environmental factors (Kwon 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The plant samples were chosen for their superior criteria compared to control, namely the age of flowering and early age of harvest and has a high yield. According to Romadhon et al (2018) genotypes with earlier flowering time will usually be able to be harvested faster. Early maturing plants are very attractive to farmers and usually the plants that flower faster will bear fruit faster.…”
Section: Determination Of Raja Bulu Banana M1v1 Generation Selected Pmentioning
confidence: 99%
“…The tomato (Solanum lycopersicum L.) plant originates from American Southern and spread in several countries such as Chile, Ecuador, and Peru (Abiso et al, 2015). Tomato can grow and develop well in lowlands (0-200 m above sea level), medium (200-500 m above sea level), and highlands (500-700 m above sea level) (Romadhon et al, 2018). Tomato fruit is essential for making tomato sauce and paste, and can be consumed fresh.…”
Section: Introductionmentioning
confidence: 99%